A NEW APPROACH TO INTERPRETATION OF SALIVARY ALFA AMYLASE ACTIVITY CHANGES AS A STRESS INDICATOR - Lubomir Petrov; Albena Alexandrova; Evtim Lefterov (Journal of Applied Sports Sciences, 2017)
Contemporary sport induces a serious physical and mental stress in athletes. This could result in lowering of their sports performance. Thus, the evaluation of stress in athletes is an important milestone in their preparation. Establishing levels of stress would allow targeted work by coaches and sports specialists to increase the resistance of competitors to stress. In this regard, the use of non-invasive methods for stress testing is essential. Recently, the use of saliva as a biological research material becomes of increasing interest. The aim of this study was to establish the potential of alpha amylase activity, protein and potassium concentrations in saliva to reflect adequately the degree of stress in athletes. Eleven boxers, participants in the National Championship, took part in the study. Saliva was collected by salivetes three times: 1) one week before the competition, 2) before the draw of lot, and 3) before the first bout. The salivary alpha amylase activity (sAA), protein and potassium concentrations were detected with commercially available kits. The sAA, protein and K+ concentrations rose significantly in stress conditions. The individual values of sAA showed large differences that could be explained by the poly-allelic expression of sAA whose activity depends on the number of alleles (2 to 14) with each individual. All tested indices could serve as indicators for evaluation of stress level in athletes as a high correlation between the protein and K+ and sAA values was found. In order to evaluate the changes in sAA and to compare the individual results be-tween athletes we suggested the sAA to be presented in relative units. The activities, measured in calm conditions long time before a competition could be assumed as a baseline and the coefficient of increase in sAA in a stressful condition could be accepted as a “stress coefficient”.